Predictors of hypervirulent Klebsiella pneumoniae infections: a systematic review and meta-analysis. (April 2023) - Namikawa, H.; Oinuma, K.-I.; Yamada, K.; Kaneko, Y.; Kakeya, H.; Shuto, T.
Summary: Background: Hypervirulent Klebsiella pneumoniae (hvKp) infections confer notable morbidity and mortality. Differential diagnosis to determine whether the infections are caused by either the hvKp or classical K. pneumoniae (cKp) strain is particularly important for undertaking optimal clinical care and infection control efforts. Aim: To identify and assess the potential predictors of hvKp infections. Methods: PubMed, Web of Science, and Cochrane Library databases were searched for all relevant publications from January 2000 to March 2022. The search terms included a combination of the following terms: (i) Klebsiella pneumoniae or K. pneumoniae and (ii) hypervirulent or hypervirulence. A meta-analysis of factors for which risk ratio was reported in three or more studies was conducted, and at least one statistically significant association was identified. Findings: In this systematic review of 11 observational studies, a total of 1392 patients with K. pneumoniae infection and 596 (42.8%) with hvKp strains were evaluated. In the meta-analysis, diabetes mellitus and liver abscess (pooled risk ratio: 2.61 (95% confidence interval: 1.79–3.80) and 9.04 (2.58–31.72), respectively; all P < 0.001) were predictors of hvKp infections. Conclusion: For patients with a history of the abovementioned predictors, prudent management, including the search for multiple sites of infection and/or metastatic spread and the enforcement of an early and appropriate source control procedure, should be initiated in consideration of the potential presence of hvKp. We believe that this research highlights the urgent need for increasing clinical awareness of the management of hvKp infections.